Smart Dice Educational Game as a Strategy to Prevent COVID-19 Transmission - Reni Asmara Ariga; Edy Ikhsan; Selviani Ariga; Fajar Amanah Ariga; Sri Budi Astuti; Hijrah Purnama Sari Ariga; Dian Maya Sari (Talenta Publisher, 2025)
COVID-19 causes pneumonia, acute respiratory syndrome, kidney failure, and even death. Transmission is very easy and fast in all age groups, children have the same risk as infected adults. This greatly affects the subsequent growth and development of school-age children. Strategies to prevent infection transmission such as improving knowledge, attitudes, and health actions. For this reason, an interesting and innovative method is needed without reducing the meaning of the information conveyed, namely smart dice educational games. The purpose of community service is to increase knowledge, change attitudes towards positivity, improve psychomotor skills, become healthy living behaviors and agents of change in their environment. Methodology with transmission prevention counseling through simulation of smart dice educational games using a designed mat, one game involves four students accompanied by one teacher, and students play according to the instructions given. Community service activities were attended by 6 teachers, 103 students at SD Muhammadiyah 01 Medan. The results of the knowledge aspect: There was a very significant increase in the category of good knowledge after the use of smart dice educational games, from 1.94% to 60.19%. Attitude aspect: There was a significant change in student attitudes from the majority agreed (77.67%) to 100%. Furthermore, the action aspect: there was a drastic increase in good preventive actions after the intervention, from 0% to 81.55%, demonstrating the effectiveness of the method in encouraging positive behavior. Integrate engaging and interactive educational approaches in delivering health information to children.